IDENTIFICATION OF FARMER INTEGRATED EMERGENCY RISK BASED ON AGRICULTURAL NURSING - Suhari, Suhari; Mashuri, Mashuri; Abidin, Zainal (Nurse and Health: Jurnal Keperawatan, 2021)
Abstract Objective: The aim of the study was to identify the integrated emergency risks of farmers based on nursing models in the agricultural area of Lumajang, Indonesia.Materials and Methods: A quantitative design with a descriptive approach was performed through the identification of threats, vulnerabilities, and capabilities in 357 farmers in integrated emergency response with cluster sampling techniques. Data was collected through questionnaires, interviews, and focus group discussions. Data analysis was carried out using the Job Safety Analysis scoring method of the Australian and New Zealand Standard on Risk Management. Results: The emergency risk of farmers based on agricultural nursing was the high category, the highest threat was direct contact with chemicals (95%), the highest contact chemicals are insecticides (57%), frequency of contact once a week (44%), and the highest vulnerability not having employment insurance (97%), the length of farming > 10 years (65%) and the length of work in 1 month 10-20 days (48%), long work on land 8-10 hours (5%) and no holiday in a month (20%), while the capability of farmers in first aid to accidents was low (44%).Conclusion: The emergency risk of farmers in Lumajang was high and the capability for emergency-response based on agricultural nursing was low. Keywords: Threats, vulnerabilities, capabilities, emergencies, farmers, agricultural nursing